Lake Bosumtwi Holiday Resort - Aidoo, Wilberforce Kwesi (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Postgraduate Diploma in Architecture, 1996